PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Herawati, Heny; Ermawati, Dwi (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
The purpose of the research in the know the leadership style and motivation that can improve employee performance so that the research will take the title: Influence of Leadership style and employee performance motivation at PT. Tae Jong Indonesia. In this study used 30 Sample respondents. The data analysis methods used are statistical tests using multiple linear regression analysis techniques, double correlation, coefficient of determination in hypotheses test. The test results of the study concluded that there was a significant influence between the leadership force on employee performance, and there was an insignificant influence between the motivation to employee performance, a known formula of multiple linear regression equations: Y = 20,170 + 0.433 X1 + 0.045 X2 with R2 value = 0.648. Proven that the leadership style and motivation to employee performance variables are 42% while the remaining 58% is influenced by other factors not researched in this study, and based on hypothesis testing results by using T-Test (partial) The result of leadership style which means leadership style Thitung > This (3.437 > 2.051) shows that Ho is rejected and H1 accepted which means leadership style is positively influential towards employee performance The motivation with the < this (0.475 < 2.051) Thitung indicates that Ho is accepted and the H1 is rejected which means that motivation has no effect on employee performance. Based on test results F (simultaneous) obtained the result of Fcountdown > Ftabel (9.776 > 3.34) showed. H1 acceptance, so it can be concluded that leadership style and motivation affect employee performance at PT. Tae Jong Indonesia.